2013
DOI: 10.5424/sjar/2013113-4060
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between udder morphology traits, alveolar and cisternal milk compartments and machine milking performances of dairy camels (Camelus dromedarius)

Abstract: A total of 22 dairy dromedary camels under intensive conditions in late lactation (275±24 days) were used to study the relationship between external and internal udder morphology and machine milking performances. Measurements of udder and teat morphology were obtained immediately before milking and in duplicate. Individual milk yield, lag time and total milking time were recorded during milking, and milk samples were collected and analyzed for milk composition thereafter. Cisternal and alveolar milk volumes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
27
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 21 publications
11
27
1
1
Order By: Relevance
“…Fat percentage in alveolar milk of Najdi sheep was greater than in cisternal milk for the 8-h milking interval during suckling and milking periods. This result agreed with those previously reported in sheep (McKusick et al, 2002b;Castillo et al, 2008), goats (Salama et al, 2004), cows and dromedary camels (Ayadi et al, 2013). The difference between milk fractions can be explained by the viscosity and large size of fat globules, which are accumulated in the alveolar compartment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Fat percentage in alveolar milk of Najdi sheep was greater than in cisternal milk for the 8-h milking interval during suckling and milking periods. This result agreed with those previously reported in sheep (McKusick et al, 2002b;Castillo et al, 2008), goats (Salama et al, 2004), cows and dromedary camels (Ayadi et al, 2013). The difference between milk fractions can be explained by the viscosity and large size of fat globules, which are accumulated in the alveolar compartment.…”
Section: Discussionsupporting
confidence: 93%
“…No significant differences were observed between milk protein, lactose and total solid percentages of cisternal and alveolar milk during suckling and milking periods. These results agree in part with those findings in dairy ewes (Rovai et al, 2008), dairy goats (Salama et al, 2004), dairy cows and lactating dromedary camels (Ayadi et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Our results were less than that reported by (Ayadi, et al) for udder measurements (cm) [29]. (Ayadi, et al), also found positive relationships were detected between milk yield and udder morphology traits of dairy camels [29].…”
Section: Teat Measurementscontrasting
confidence: 97%
“…In accordance with the present results in this study, (Ayadi, et al) and Abdallah and Faye found that teat length showed similar values in different breeds of camel in Saudi Arabia [26,29]. Meanwhile, the distance between teats was greater than the results previously reported by (Eisa, et al) on camel [27].…”
Section: Teat Measurementssupporting
confidence: 92%
See 1 more Smart Citation